2014
DOI: 10.1111/1462-2920.12606
|View full text |Cite
|
Sign up to set email alerts
|

Interclonal gradient of virulence in the Pseudomonas aeruginosa pangenome from disease and environment

Abstract: SummaryThe population genomics of Pseudomonas aeruginosa was analysed by genome sequencing of representative strains of the 15 most frequent clonal complexes in the P. aeruginosa population and of the five most common clones from the environment of which so far no isolate from a human infection has been detected. Gene annotation identified 5892-7187 open reading frame (ORFs; median 6381 ORFs) in the 20 6.4-7.4 Mbp large genomes. The P. aeruginosa pangenome consists of a conserved core of at least 4000 genes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
142
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 101 publications
(160 citation statements)
references
References 58 publications
13
142
0
Order By: Relevance
“…This observation is in line with other studies that found the isolation source of a bacterial strain not to be predictive for its performance in another habitat (Alonso et al, 1999;Grosso-Becerra et al, 2014). For instance, Hilker and colleagues found no correlation between original habitat and virulence in different test systems for clinical and environmental clones of P. aeruginosa (Hilker et al, 2015). In general, fluorescent pseudomonads might be quite ubiquitous and probably possess an arsenal of traits allowing them to easily switch niches and to conquer the habitat they encounter.…”
Section: Discussionsupporting
confidence: 82%
“…This observation is in line with other studies that found the isolation source of a bacterial strain not to be predictive for its performance in another habitat (Alonso et al, 1999;Grosso-Becerra et al, 2014). For instance, Hilker and colleagues found no correlation between original habitat and virulence in different test systems for clinical and environmental clones of P. aeruginosa (Hilker et al, 2015). In general, fluorescent pseudomonads might be quite ubiquitous and probably possess an arsenal of traits allowing them to easily switch niches and to conquer the habitat they encounter.…”
Section: Discussionsupporting
confidence: 82%
“…The sequencing of the PCR-amplified DNAs of the CF strain panel revealed 1,908 different sequence variants (SNPs) (see Table S3 in the supplemental material) compared to the PA14 reference genome; i.e., nucleotide substitutions occurred at least once at 7.1% of the sites (Table 1). A portion consisting of 796 SNPs (41.7% of total) had already been observed in the P. aeruginosa pangenome of the 20 most common clones in the P. aeruginosa population (24). The average sequence diversity of the concatenated 17 loci between an individual CF isolate and the PA14 reference was determined to be 0.81%, which fits with the global sequence diversity of the core genome of 0.85% between the PAO1 and PA14 reference genomes (24).…”
Section: Resultsmentioning
confidence: 66%
“…The 21 49-strain pools were then subjected to amplicon sequencing. The obtained sequences of the CF strain panel were compared with those of the PA14 reference genome and the 20 most common clone types (24) in order to identify those sequence variants of the CF data set which had already been detected in other habitats and thus are not specific for the niche of the CF airway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations